Trends in Effective Diffusion Coefficients for Ion-Exchange Strengthening of Soda-Lime-Silicate Glasses - Karlsson, Stefan; Wondraczek, Lothar; Ali, Sharafat; Jonson, Bo (Frontiers in Materials, 2017)
Monovalent cations enable efficient ion exchange processes due to their high mobility in silicate glasses. Numerous properties can be modified in this way, e.g., mechanical, optical, electrical or chemical performance. In particular, alkali cation exchange has received significant attention, primarily with respect to introducing compressive stress into the surface region of a glass, which increases mechanical durability. However, most of the present applications rely on specifically tailored matrix compositions in which the cation mobility is enhanced. This largely excludes the major area of soda lime silicates (SLS) such as are commodity in almost all large-scale applications of glasses. Basic understanding of the relations between structural parameters and the effective diffusion coefficients may help to improve ion-exchanged SLS glass products, on the one hand in terms of obtainable strength and on the other in terms of cost. In the present paper, we discuss the trends in the effective diffusion coefficients when exchanging Na+ for various monovalent cations (K+, Cu+, Ag+, Rb+ and Cs+) by drawing relations to physico-chemical properties. Correlations of effective diffusion coefficients were found for the bond dissociation energy and the electronic cation polarizability, indicating that localization and rupture of bonds are of importance for the ion exchange rate.